2007
DOI: 10.1021/jo701561d
|View full text |Cite
|
Sign up to set email alerts
|

Axially Chiral BINIM and Ni(II)-Catalyzed Highly Enantioselective 1,3-Dipolar Cycloaddition Reactions of Azomethine Ylides and N-Arylmaleimides

Abstract: Axially chiral BINIM-Ni(II) complexes are effective catalysts in the asymmetric 1,3-dipolar cycloaddition reactions of azomethine ylides and N-arylmaleimides to give the corresponding adducts in good yields and up to 95% enantiomeric excesses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
38
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(40 citation statements)
references
References 27 publications
1
38
0
1
Order By: Relevance
“…Ligand 1 e, bearing two bromine atoms at the 3,3'-positions of the TF-BiphamPhos backbone, emerged as the most effective chiral ligand and provided endo-4 a in high yield and excellent enantioselectivity of 96 % (Table 1, entry 6). A subsequent survey of solvent effects indicated that EtOAc was the solvent of choice in terms of the reactivity and enantioselectivity (Table 1, entries [6][7][8].…”
mentioning
confidence: 99%
“…Ligand 1 e, bearing two bromine atoms at the 3,3'-positions of the TF-BiphamPhos backbone, emerged as the most effective chiral ligand and provided endo-4 a in high yield and excellent enantioselectivity of 96 % (Table 1, entry 6). A subsequent survey of solvent effects indicated that EtOAc was the solvent of choice in terms of the reactivity and enantioselectivity (Table 1, entries [6][7][8].…”
mentioning
confidence: 99%
“…The [3+2] cycloaddition reaction of azomethine ylide with olefinic dipolarophiles constitutes a straightforward approach to the synthesis of highly substituted chiral pyrrolidine derivatives. [34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50] So far, many laboratories have reported the catalytic asymmetric [3+2] cycloadditions with azomethine ylides by means of a variety of ligand-metal combinations. Our group reported that the ferrocenyloxazoline derived chiral N,P ligand showed excellent performance in the Ag(I)-catalyzed enantioselective 1,3-dipolar cycloaddition of azomethine ylides.…”
Section: Resultsmentioning
confidence: 99%
“…Condensed ring substrates 1 f and 1 g also gave the desired products 2 f and 2 g in high yields and with 96 % ee and 92 % ee, respectively (Table 2, entries 6 and 7). The electronrich substituents on 1 h-1 j underwent the IOM addition and decarboxylation processes to yield the enantiomeric adducts (2 h-2 j) in excellent yields and with ee values in the range 84-93 % ee ( Table 2, entries [8][9][10]. The aliphatic substrate 1 k was also found to be suitable, affording chromanone 2 k in 90 % yield and with 85 % ee (Table 2, entry 11).…”
mentioning
confidence: 98%